Community-level analysis of the microbiology in constructed wetlands treating distillery effluent - Du Plessis, Keith R. (Keith Roland) (Stellenbosch : University of Stellenbosch, 2011)
Dissertation (PhD)--University of Stellenbosch, 2006.